Water droplets impact dynamics on laser engineered superhydrophobic ceramic surface. (February 2023) - Radhakrishnan, J.; Diaz, M.; Cordovilla, F.; Kopecek, J.; Ocaña, José L.
Highlights: Laser-engineered surface structures promotes the breakdown of the water droplets. Hydrodynamics is modified by surface geometry with porous, spongy structures. Rapid wetting property transition from Hydrophilic to superhydrophobic in four hours. Optimal depth for superwetting hierarchical surface structures is of around 1 μm. Abstract: The development of superhydrophobic surfaces is significant due to the industrial applications in various fields, from energy to biomedical implants. The surface morphology and chemistry primarily govern the characteristics of the interface between the water droplet and the surfaces. Herein, a combination of laser patterning and low-pressure technique has been adopted to generate the superhydrophobic TiN surface. The superhydrophobic surface was subjected to wetting property and chemical analysis with respect to the surface geometry. The impact dynamics of water droplets at the laser-patterned superhydrophobic surface have been studied. The droplet impacts result in finger formation at the start of the spreading, and the droplets formed at the tip of fingers detached from the rim during the retraction. The resulting fragmentation favors decreased travel distance and time required for recoiling the water droplets. The fragmentation during the recoiling results from modified hydrodynamics induced by the surface morphology and wetting property. The laser-processed hierarchical surface structures are a potential method to reduce the contact time at the solid-liquid interface.